2012
DOI: 10.1111/j.1472-4642.2011.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Humans alter habitat selection of birds on ocean‐exposed sandy beaches

Abstract: Aim  Resource‐selection functions (RSFs) can quantify and predict the density of animal populations across heterogeneous landscapes and are important conservation tools in areas subject to human disturbance. Sandy beach ecosystems have comparatively low habitat heterogeneity and structural relief in the intertidal zone, but intense human use. We aimed to develop predictive RSFs for birds on ocean‐exposed sandy beaches at two spatial scales, 25 ha (local scale) and 250 ha (landscape scale), and to test whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 72 publications
0
50
0
2
Order By: Relevance
“…We found that terrestrial avian scavengers had consumed nearly all of the fish carrion deposited on the beach within a week. Two factors appear most likely to contribute to this rapid and efficient scavenging on sandy beaches: a) raptors and other avian scavengers are abundant along the shoreline [69,70], and appear to have a specific search behaviour where individuals fly parallel to the base of the dunes where most carrion naturally strands (Schlacher, pers. obs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that terrestrial avian scavengers had consumed nearly all of the fish carrion deposited on the beach within a week. Two factors appear most likely to contribute to this rapid and efficient scavenging on sandy beaches: a) raptors and other avian scavengers are abundant along the shoreline [69,70], and appear to have a specific search behaviour where individuals fly parallel to the base of the dunes where most carrion naturally strands (Schlacher, pers. obs.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic factors may be influential in highly disturbed areas. However, seldom have the interactions of all three of these factors been studied simultaneously, although several studies have attempted to discriminate their relative importance (Burger and Gochfeld, 1991;Gallant et al, 2009;Mahan and Yahner, 1996;Meager, Schlacher, and Nielsen, 2012;Peters and Otis, 2007). Work on river otters (Lontra canadensis), for example, suggested that environmental factors were more influential than anthropogenic factors in describing habitat selection patterns, but anthropogenic disturbances could indirectly affect habitat selection of otters by causing the loss of important habitat features (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The sites were selected based on four attributes particularly relevant for the study of interactions between vehicles and birds: 1) the eastern shores of both islands feature long stretches of exposed sandy beaches [32], 2) dunes and beaches of both islands are important feeding, roosting, and breeding sites for coastal birds [17,33,34], 3) motorised traffic is very intense on the beaches [35], and 4) this heavy traffic, most of it recreational, causes substantial disturbance to birds [20], resulting in conservation concerns about the impacts of traffic on birds and other wildlife [36,37]. …”
Section: Methodsmentioning
confidence: 99%
“…Our procedure of ranking disturbance response on an ordinal scale resembles methods used in similar bird-human interaction studies [40,41]. We also recorded the following contextual variables: number of individuals in the flock, beach width (m), wind speed (km h -1 ), temperature (°C), and state of the tide (hours since low water); these variables could potentially influence bird behaviour [17,20,32]. Focal observations lasted for 30 minutes or until an encounter with a vehicle, whichever came first.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation